2020
DOI: 10.34175/jno202003005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weight Loss on Survival in Esophageal Cancer Patients undergoing Neoadjuvant Chemoradiotherapy and Surgery

Abstract: 12], the impact of weight loss during neoadjuvant CRT on the long-term survival of patients with esophageal cancer remains unknown. Therefore, this retrospective study aimed to investigate the association of weight loss during neoadjuvant CRT with survival outcomes in patients with esophageal cancer. Materials & Methods Study design and participants A total of 102 patients with esophageal squamous cell cancer undergoing neoadjuvant CRT followed by surgery at Sichuan Cancer Hospital & Institute from March 2003 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…6,7 However, radiotherapy has toxic side effects in patients and might also lead to malnutrition. 8 Long-term malnutrition reduces the quality of life of patients and their tolerance to radiotherapy and decreases treatment sensitivity, resulting in prolonged hospitalization or shortened survival time, or in severe cases, treatment failure due to lack of tolerance. 9,10 Some studies have shown that cancer patients always have negative emotions, and almost 50% of cancer patients suffer from anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, radiotherapy has toxic side effects in patients and might also lead to malnutrition. 8 Long-term malnutrition reduces the quality of life of patients and their tolerance to radiotherapy and decreases treatment sensitivity, resulting in prolonged hospitalization or shortened survival time, or in severe cases, treatment failure due to lack of tolerance. 9,10 Some studies have shown that cancer patients always have negative emotions, and almost 50% of cancer patients suffer from anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%